Augmented reality vs. monetary rewards: which drives pro-environmental behavior more effectively among the Indonesian workforce? - Herlina, Maria Grace; Ozgen, Eren; Iskandar, Karto (Business, Management and Economics Engineering, 2026)
Purpose – This study examines how augmented reality-based green training influences pro-environmental behavior among employees in Greater Jakarta, Indonesia. It also examines the role of green commitment in shaping employees’ environmentally responsible actions. In addition, the study investigates whether green financial rewards moderate these relationships. The analysis focuses on how intrinsic and extrinsic motivations interact to influence sustainable behavior in the workplace. Research methodology – A cross-sectional quantitative survey was conducted among 200 employees in Greater Jakarta using convenience sampling. Structural equation modeling with partial least squares was used to test the hypothesized relationships and moderating effects among the variables. Findings – The findings show that AR-based green training has a significant positive effect on employees’ pro-environmental behavior. Green commitment also has a significant positive effect on pro-environmental behavior. Green financial rewards do not significantly moderate these relationships. The negative interaction coefficients suggest a possible crowding out effect. This implies that in practice, external motivators may dampen the effect of internal motivators, such as training and employee engagement. Research limitations – The design of this study is cross-sectional, and this restricts the ability to conduct causal analysis. The population studied can only comprise employees within greater Jakarta, and this might restrict the overall ability to generalize findings. Future re- search focuses on studying changes over longer periods through various designs that can aid in observations over time. Results can also gain more external validity if more demographical samples get studied. Practical implications – Implementation of organizational measures to increase the qualifications and sustainability-oriented working culture could provide the greatest benefits for the organizations. Moreover, incorporating augmented reality learning into the organizational operations could contribute to this goal. In addition, values associated with sustainability must be embedded into the organizational operations through persistent organizational communications and role-modeling by the leadership. It can be observed from the outcome measurements that the financial incentives are less effective or sometimes even decrease the internal motivation associated with pro-environmental behavior. Originality/Value – The research adds to the topic of sustainability studies by focusing on the use of augmented reality as a novel approach to environmental education. The work also supplies empirical evidence concerning the boundary conditions of the Motivation Crowding Theory within a workplace sustainability setting.